Study on prevalence of maternal risk factors, morbidity and mortality in very low birth weight neonates - Keskar, Ujjwala S.; Parekh, Anjali H. (International Journal of Contemporary Pediatrics, 2021)
Background: Very low birth weight babies with respiratory complications are the commonest reason for admission in NICU. We wanted to identify maternal risk factors associated with it and ways to prevent it. The objective of the current study was to study the prevalence of maternal risk factors, morbidity and mortality in VLBW babies admitted in tertiary care hospital NICU. Methods: Cross sectional observational study performed on all very low birth weight (VLBW) neonates admitted in neonatal intensive care unit of tertiary care hospital attached with Smt. Kashibai Navale medical college, Pune from January 2019 to March 2020. Results: In our study VLBW babies were 2.2% (78/3545). Mean gestational age was 31.15±3.21 weeks; mean birth weight was 1226.24±250.95 grams. Small for gestational age (SGA) babies were 41% and 96% were preterm. Maternal risk factors were present in 61.53% of deliveries, commonest were anaemia in 30.06 % and preeclampsia in 24.35%. Resuscitation at birth was required in 30.76% babies. Morbidity profile showed respiratory distress syndrome in 46.15%, neonatal sepsis in 19.23% and patent ductus arteriosus in 16.66% babies. Overall survival was 74.35%. Prematurity and its complications like RDS requiring surfactant therapy and mechanical ventilation were significant contributors for mortality but only 23.07% mothers were found to have received antenatal steroids in the hospital . Conclusions: Anaemia and preeclampsia were commonly found risk factors present in 61.53% of mothers of VLBW babies. Use of antenatal steroids in mothers should be made compulsory to decrease mortality in VLBW preterm newborns.